Spleen-Preserving Surgery in Treatment of Large Mesothelial Splenic Cyst in Children - A Case Report and Review of the Literature - Zlatan Zvizdić; Kenan Karavdić (Biomolecules & Biomedicine, 2013)
The nonparasitic primary splenic cysts are very rare clinical entity. In the past, splenectomy was the treatment of choice but with the recognition of the spleen’s important immunological function, spleen-preserving surgery is the preferred treatment modality. We hereby present a case of a large splenic mesothelial cyst and its treatment with preservation of the remaining splenic parenchyma. Our case shows that spleen-preserving surgery in treatment of the large splenic cysts is possible and safe procedure with maintenance of the splenic function.